Pseudo-Skylax's Periplous : the Circumnavigation of the Inhabited World: Text, Translation and Commentary. - Shipley, Graham (Liverpool University Press, 2020)
The text of the Periplous or 'circumnavigation' is a highly significant geographical text by a 4th century BC author. It describes the coasts of the Mediterranean and Black Sea, and may have been written to demonstrate the size of the inhabited world of the ancient Greeks. This revised edition contains the text and translation, with full commentary.